Alignment: / How to get your people, strategy, and culture on the same page. - Taylor, C. Anthony (Vancouver, Canada : Anthony Taylor, 2017)
This book shows how one can make it possible for an organization by creating environment where both your organization and your employees thrive.
osa 10/01/2019, ijb, 28/01/2019
Loans
Keywords: Strategic planning